A novel hybrid model for selection of benchmarking technique in Indian service industries. (2017) - Singh, Bhupender; Grover, Sandeep; Singh, Vikram
The necessity of industries for ascending their standards in competitive market occurs in convention of benchmarking techniques and to adopt new modern methods for effective system. The rationale of this study is to review the benchmarking techniques, moreover to rank them on the basis of applications in service industries. The authors have done abundant survey which identified seven different benchmarking techniques for Indian service industries. Thus, it becomes more complex to select the best one of the benchmarking techniques for implementation in industries. To rank the different benchmarking techniques, a hybrid methodology of analytical network process (ANP), technique for order preference by similarity to ideal solution (TOPSIS) and multi-objective optimisation on basis of ratio analysis (MOORA) is used. A novel hybrid model of these three MCDM is applied for prioritising the benchmarking techniques in the Indian scenario. With application of hybrid model, ranking of best alternative is obtained with fewer calculations and simple validation. Thus, endeavour has been made by authors to give a model for evaluation of benchmarking techniques through MCDM approaches which gives confidence for executives to adopt benchmarking for achieving their goals in their industries.